Pregnant Women's Knowledge and Desire Towards Labor Companionship and its Associated Factors at Public Hospitals in South Wollo Zone, Northeast Ethiopia - Zenebe Tefera; Mandefro Assefaw; Wondimnew Gashaw; Sindu Ayalew; Endalk Birrie; Mulugeta W/Selassie; Girma Wogie (Mashhad University of Medical Sciences, 1999)
Background & aim: Companionship in labor is highly effective in encouraging facility-based delivery and has a positive effect on maternal self-control during childbirth. However, there have been few studies in Ethiopia to examine this issue. Therefore, this study assessed pregnant women's knowledge and desire towards labor companionship and its associated factors at public hospitals in South Wollo Zone, Northeast Ethiopia.Methods: A facility-based cross-sectional study design was employed from 1st November to 9th December, 2020. Study participants consisted of 416 pregnant women, who were selected by a systematic random sampling technique. Data were collected using structured questioners including socio-demographic characteristics, obstetric history, knowledge and desire towards companionship in labor, through face-to-face interviews.Results: In this study, 19.5% of respondents have good knowledge while 87.3% of them have desire to have labor companion.  Diploma and higher educational level (AOR=3.23 95% CI: 1.06, 9.86), prior birth at private health-facility AOR=3.95, 95% CI: 1.08, 7.49) and having the experience of previous labor companion (AOR=2.36, 95% CI: 1.27, 4.38) were significantly associated with good knowledge. Rural residence (AOR=6.8, 95% CI: 1.40, 9.99) and history of having labor companion (AOR=5.34, 95% CI: 1.53, 9.64) were associated with desire to have companion.Conclusion: Small percentage of pregnant women had awareness on labor companionship while a large percentage of women desire companionship during childbirth. Therefore, health care professionals should educate perinatal women about labor companions and allow them to have a support person throughout labor and delivery at a health facility to increase their awareness and desire.